2017
DOI: 10.1007/s10460-017-9834-4
|View full text |Cite
|
Sign up to set email alerts
|

Off to market: but which one? Understanding the participation of small-scale farmers in short food supply chains—a Hungarian case study

Abstract: The research described in this paper was designed to identify the factors that influence the importance small-scale farmers place on different marketing channels of short food supply chains. The focus concerns two entirely different types of market that are present in the bigger cities in Hungary: 'conventional' markets where there are no restrictions on locality but the farmer-market relationship is based on binding contracts, and newly-emergent farmers' markets at which only local growers can sell ad hoc, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 51 publications
3
66
1
Order By: Relevance
“…Obtaining funds from the buyers before harvest allows for the farmers in the CSA program to carry lower financial debts, and allows them to recover from possible low yields due to weather uncertainties. The shared responsibility by CSA members is one of the main differences between a CSA and a vegetable box scheme [4,14].…”
Section: Csa Farmers' Motivations and Expectationsmentioning
confidence: 99%
“…Obtaining funds from the buyers before harvest allows for the farmers in the CSA program to carry lower financial debts, and allows them to recover from possible low yields due to weather uncertainties. The shared responsibility by CSA members is one of the main differences between a CSA and a vegetable box scheme [4,14].…”
Section: Csa Farmers' Motivations and Expectationsmentioning
confidence: 99%
“…The lack of education also reflects in the absence of sustainable agriculture, the usage of pesticide, and the ignorance of biodiversity (Chen and Zheng, 2016). It can be noted that in developed countries farmers' motivations of participating in SFSCs are mainly spontaneous, such as reducing energy consumption (Smith, 2008), improving biodiversity (Canfora, 2016), and regaining the profits shared by intermediates (Benedek et al, 2017). However, although Chinese farmers enjoyed some typical advantages of SFSCs, such as increased profit and direct communication with customers, their participations in SFSCs are more like a passive choice, as they tend to have rather limited knowledge of SFSCs and its benefits.…”
Section: Comparison With Existing Studiesmentioning
confidence: 99%
“…The most widely acknowledged social benefits of SFSCs in existing studies are identified as the improved food quality and security (Hinrichs, 2000;Marsden et al, 2000;Hinson and Bruchhaus, 2008;Smith, 2008;Jones and Bhatia, 2011;Bimbo et al, 2015;Engelseth, 2016;Leiper and Sather, 2017), additional employment opportunities (Ilbery and Maye, 2005;Sgroi et al, 2014;Falguieres et al, 2015;Tudisca et al, 2015;Mundler and Laughrea, 2016;Rover et al, 2017), and the regained consumers' trust (Hinson and Bruchhaus, 2008;O'Kane and Wijaya, 2015;Giampietri, 2016;Giampietri, 2018). Meanwhile, the friendly shopping atmosphere (Hinson and Bruchhaus, 2008;Watts et al, 2011;Zirham and Palomba, 2015;Benedek et al, 2017;Leiper and Sather, 2017) and the social connection with customers and fellow farmers (Beckie et al, 2012) are also noted as the improved social sustainability of SFSCs. Based on the results from the conducted pilot study, it can be noted that a high correlation can be found on the farmers' opinions on this social pillar.…”
Section: Comparison With Existing Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Work on consumers' behavior towards these chains shows a consistent focus on the motives driving participation in such production—consumption lines (Giampietri et al ., 2016; Hashem et al ., 2018). On the other hand, the antecedents of farmers' participation in SFSCs have received only a small share of attention (Benedek et al ., 2018; Charatsari et al ., 2018 a ). However, to further support the development of alternative food networks (AFNs), an important question to be answered is how to increase farmers' participation in such initiatives (Bruce and Som Castellano, 2017).…”
Section: Introductionmentioning
confidence: 99%